2018
DOI: 10.1021/acs.jmedchem.8b01018
|View full text |Cite
|
Sign up to set email alerts
|

Tanshinone-IIA-Based Analogues of Imidazole Alkaloid Act as Potent Inhibitors To Block Breast Cancer Invasion and Metastasis in Vivo

Abstract: Tanshinone-IIA (Tan-IIA), a primary active component extracted from commonly used Chinese herbal, Salvia miltiorrhiza (Danshen), is considered as a potential inhibitor against tumor cell proliferation. However, the potential application of Tan-IIA is hindered by its poor water solubility and low bioavailability. In this work, an imidazole moiety was linked to the skeleton of Tan-IIA to enhance its antitumor activity. A series of Tan-IIA-based analogues TA01–TA12 were synthesized, and their inhibitory activitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(21 citation statements)
references
References 50 publications
0
21
0
Order By: Relevance
“…Of the tanshinone family, previous studies have demonstrated that tanshinone IIA could induce apoptosis in both ER-positive and ER-negative breast cancers (Wang et al, 2005; Su and Lin, 2008; Su et al, 2012; Yan et al, 2012; Lin et al, 2013; Fu et al, 2014; Li et al, 2015; Li and Lai, 2017; Lin et al, 2018; Lv et al, 2018; Wu et al, 2018). Tanshinone I also exerts a similar anti-breast cancer effect through apoptosis (Nizamutdinova et al, 2008a; Nizamutdinova et al, 2008b; Gong et al, 2012; Wang et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the tanshinone family, previous studies have demonstrated that tanshinone IIA could induce apoptosis in both ER-positive and ER-negative breast cancers (Wang et al, 2005; Su and Lin, 2008; Su et al, 2012; Yan et al, 2012; Lin et al, 2013; Fu et al, 2014; Li et al, 2015; Li and Lai, 2017; Lin et al, 2018; Lv et al, 2018; Wu et al, 2018). Tanshinone I also exerts a similar anti-breast cancer effect through apoptosis (Nizamutdinova et al, 2008a; Nizamutdinova et al, 2008b; Gong et al, 2012; Wang et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…These data suggested that danshen may have a clinical protective effect for patients with both ER-positive and ER-negative breast cancer owing to the constituent abietane diterpenes. Moreover, some studies have demonstrated that, in combination with tanshinone IIA, danshen could enhance the chemosensitivity of breast cancer cells to chemotherapy and even overcome drug-resistant cancer (Li and Lai, 2017; Lin et al, 2018; Lv et al, 2018; Wu et al, 2018). Further research to investigate the clinical protective effect of danshen combined with other breast cancer medication is necessary.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, the abnormal expression of tumor related genes, abnormal activation of cell signal transduction, cell proliferation cycle, and cell proliferation cycle were also involved in many aspects [15][16][17]. Cell growth and proliferation in human body are affected and controlled by many factors [18,19]. In particular, cell signaling proteins, growth factors and their receptors, apoptotic proteins and transcription factors, etc, and the changes of these factors are closely related to the occurrence and development of tumor [20,21].…”
Section: Discussionmentioning
confidence: 99%
“…Nutlins-1, which has imidazole as a pharmacophore, displaces recombinant p53 protein from its complex with MDM2 and selectively inhibits MDM2-p53 interaction both in vitro and in vivo [ 15 ]. The antitumor potency of Tanshinone-IIA has been enhanced by the introduction of an imidazole moiety ( Figure 1 , TA12) in order to block cancer cell invasion and metastasis in vivo [ 16 ]. N -phenylimidazole (NMIB) possesses outstanding cytotoxic activity [ 17 ].…”
Section: Introductionmentioning
confidence: 99%